2020
DOI: 10.3389/fonc.2019.01438
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of PET/CT Using 18F-FACBC in Prostate Cancer: A Meta-Analysis

Abstract: Background: Diagnostic performance of PET/CT using 18F-fluciclovine (18F-FACBC) in patients with prostate cancer (PCa) has been evaluated in only a few studies. There is no consensus on the diagnostic value of 18F-FACBC PET/CT in PCa recurrence or metastasis (except for bone metastasis), the primary diagnosis of the lesion. Hence, a meta-analysis was conducted to evaluate the performance of 18F-FACBC PET/CT. Methods: The literature published from June 2015 to June 2019 on using 18F-FACBC PET/CT for the diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In some meta-analyses, diagnostic accuracy of 18 F-FACBC PET/CT was reported as moderate: higher in the staging than restaging setting [ 8 , 32 , 33 , 34 , 35 , 36 ]. In the first meta-analysis by Ren et al [ 36 ], 18 F-FACBC PET/CT demonstrated a pooled sensitivity and pooled specificity of 87% and 66%, respectively, in detecting BR-PCa.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some meta-analyses, diagnostic accuracy of 18 F-FACBC PET/CT was reported as moderate: higher in the staging than restaging setting [ 8 , 32 , 33 , 34 , 35 , 36 ]. In the first meta-analysis by Ren et al [ 36 ], 18 F-FACBC PET/CT demonstrated a pooled sensitivity and pooled specificity of 87% and 66%, respectively, in detecting BR-PCa.…”
Section: Resultsmentioning
confidence: 99%
“…Another two recent meta-analyses [33,34] confirmed the good sensitivity (86-88%) and moderate specificity (73-76%) of 18 F-FACBC PET/CT in staging and restaging PCa.…”
Section: F-facbc (Fluciclovine) Pet/ctmentioning
confidence: 88%
See 2 more Smart Citations
“…18F-fluciclovine is more practical to handle than 11C-choline because of a physical half-life of 110 min for the former compared to 20 min for the latter [55,56]. Moreover, 18Ffluciclovine exhibits little renal excretion or bladder uptake compared to 11C-choline, allowing for better visualization of the prostate and greater accuracy of detection of involved sites in distant lymph nodes [57]. This increase in accuracy was demonstrated by Nanni et al [58] who showed that 18F -fluciclovine was statistically significantly superior to 11Ccholine in detecting both local and distant sites of disease recurrence.…”
Section: Treatmentmentioning
confidence: 99%